Coronary blood flow velocity measurement from X-ray cineangiograms - Wang, Yingjian. (2009)
Derivation of the blood flow map of the heart is very useful for diagnosis and therapy of heart-related diseases. There are three main methods of measuring blood flow velocity: the Laser Doppler technique, the Ultrasonic Doppler technique, and the Image Processing technique. The former two are based on Doppler effect and the last one utilizes computer-assisted digital image processing technique. Digital image processing provides a powerful and promising method for estimation of blood flow.